Feasibility and Operational Limits for a 236 GHz Hollow-Cavity Gyrotron for DEMO - Kalaria, Parth Chandulal (KIT Scientific Publishing, 2017)
The DEMOnstration fusion power plant (DEMO) will be the first fusion reactor, which is intended to generate net electrical power. For successful operation of DEMO, high-power gyrotrons with operating frequencies up to 240 GHz are required for plasma heating and stabilization. In this work, a systematic feasibility study and tolerance analysis are performed for the conventional-type hollow-cavity DEMO gyrotrons. The various approaches are also suggested to identify its operational limits.
English
Keywords: Hollow-cavity; Hohlleitergyrotron; Kernfusion; Frequenz durchstimmbarkeit; Gyrotron; DEMO; Nuclear Fusion; Frequency Tunability